Programming paradigms concept / Jamal Othman ... [et al.] - Othman, Jamal; Ahmad, Jasmin Ilyani; Abdul Wahab, Naemah; Che Jan, Nora Yanti; Abd Wahab, Zawawi Ismail (UiTM Press, 2019)
Programming languages have gone through several paradigms since 1940s. The researchers have done many innovations to introduce new programming language which is easier to understand and compatible with any platforms of Operating Systems (OS) and machines. Now, the aim or the vision of future programming language is to help novice programmers to write codes using natural language such as English language or any selected language. Life becomes easier and difficulties in understanding the programming language is not the main reason anymore. This book has been organised accordingly to paradigm of programming language from imperative paradigm to object-oriented, functional, logic and several other important paradigms. All students have been exposed to basic programming paradigm such as structured programming which represents the imperative paradigm. In the following semester, students will be introduced to object-oriented programming paradigm with several important concepts such as abstraction, inheritance, polymorphism, encapsulation and information hiding. All these concepts should be liaised to the similar concepts in the imperative paradigms and other paradigms as well.